Thermo-hydraulic optimization of rectangular duct solar air heaters using equilateral triangular roughness on absorber plates - Sastry, G. R. K.; Raju, L. B. Bharath; Gugulothu, S. K.; Agbulut, Uemit; Barmavatu, Praveen (SPRINGER, 2025)
Turbulence promoters are a widely used strategy to improve the working of solar air heaters in many industrial applications. This paper demonstrates the improvement in turbulent air due to the breakage of laminar sublayers by inserting a quadrilateral-shaped solar air heater with turbulence promoters (having an equilateral triangle shape) on the absorber plate. The performance of the proposed solar air heater is evaluated numerically with the computational fluid dynamics for the considered parameters. A comprehensive study is done to determine the impact of rib height (0.021-0.042), rib pitch (10-25), and relative roughness pitch (7.14-35.71) on the heat transfer parameters, as measured by the THPP. The findings demonstrate that the equilateral triangle roughness features create longitudinal vortices and establish areas of flow impingement, which substantially impact the flow and heat transfer properties of the air within the solar air heater. The heat transfer improved by 141% with the use of the turbulence promotors over the simple system without turbulators. The maximum performance characteristics of the system correspond to the e/D of 0.042 with a P/e of 7.14 at a Reynolds number of 15,000. Empirical correlations are employed to find the relation between Nu and f, which predicted the values with an average deviation of 4.25% and 2.45%, respectively.
Keywords: Triangular ribs; SAH; Re number; Roughness height; Nusselt number; THPP; COMPUTATIONAL FLUID-DYNAMICS; RIB ROUGHNESS; FRICTION FACTOR; PERFORMANCE IMPROVEMENT; HYDRAULIC PERFORMANCE; TRANSFER AUGMENTATION; EFFECTIVE PARAMETERS; FLOW CHARACTERISTICS; TRANSFER ENHANCEMENT; SENSITIVITY-ANALYSIS; Thermodynamics; Chemistry